Improving The Methodology Of Teaching Social And Humanitarian Sciences To Students On The Base Of A Competent Approach (Example Of Pedagogical Diagnostics And Correction Science) - Khalmatova D.A. (Euro Asian Journal Publishing, 2024)
This article talks about what competence students of the Pedagogical University have in the conditions of development and what teaching methods they choose in practice. Pedagogical qualities and content of training that should be acquired for future pedagogues are highlighted
Keywords: Student; socio-humanitarian; sciences; competence